Implementation of Education and Internalization of Pancasila Values Through a Visit To Pancasila Balun Lamongan Village For Secondary Students in Lamongan District - Burhan Hakim, Ahmad; Akmalul Umam (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
Pancasila is one of the basic ideologies of the Indonesian state which has long had social values ​​and norms that have become the nation's identity. So that Pancasila has an important position in maintaining the integrity of the Republic of Indonesia (the unitary state of the Republic of Indonesia). Implementation and internalization of the values ​​contained in Pancasila are not enough to just be taught normatively in the classroom such as learning and teaching activities. There needs to be a new touch so that students learn Pancasil with enthusiasm. A visit to Pancasila Balun Village, Lamongan Regency, East Java, is an alternative for this new touch. With this visit, students were able to empirically see and assess how and what kind of values ​​in Pancasila are applied in society, especially the Lamongan community itself. A visit to Balun Village is not without reason, but because of the harmony and tolerance that exist in the village, making it interesting to visit. This research uses qualitative research methods by collecting primary data through interviews and observations at the location of the visit, namely Pancasila Balun Village. In this village there are three religions adhered to by the people in the village, namely Islam, Protestant Christianity and Hinduism. Harmony in the village has been maintained for a long time and there has almost never been any conflict involving religious adherents. For us, it is this value that is worthy of being used as an example by students to find out what it is like and how to implement and internalize Pancasila values ​​in an applied manner, not just theoretically as has been taught in the classroom.